Electrical stimulation and piezoelectric biomaterials for bone tissue engineering applications - Khare, Deepak; Basu, Bikramjit; Dubey, Ashutosh Kumar (Biomaterials, 2020)
Bioelectrical phenomenon in natural bone has been well recognized for its role in bone development and fracture healing. For example, the piezoelectricity induced modulation in cellular functionality assists in the repair and regeneration of bone tissue. Against this backdrop, we review here the origin of dielectric and electrical responses (piezo-, pyro- and ferro-electricity) of natural bone along with their consequences in regulating the bone metabolic activities. The concept of piezoelectricity induced osteogenesis has driven the development of piezoimplants for bone regeneration applications. A number of recent studies have been critically analyzed to demonstrate as to how the surface charge polarization or electric field stimulation together with functional properties of piezoelectric biomaterials can synergistically modulate cell functionality, in vitro or tissue regeneration, in vivo. The examples are drawn from a range of piezoelectric bioceramics, (e.g. barium titanate, magnesium silicate etc.) and biopolymers (e.g. polyvinylidene fluoride (PVDF), collagen, etc). The challenging problem of processing the compositionally tailored bioceramics is emphasized in particular reference to (Na, K)NbO3, an implantable biomaterial with the most attractive combination of piezoresponsive properties. Taken together, this review comprehensively emphasizes the appealing relevance of piezo-bioceramics and piezo-biopolymers as next-generation orthopedic biomaterials.